The emerging role of neutrophils in autoimmune‐associated disorders: effector, predictor, and therapeutic targets. Issue 3 (22nd July 2021) - Fu, Xiaohong; Liu, Heting; Huang, Gang; Dai, Shuang‐Shuang
Abstract: Neutrophils are essential components of the immune system and have vital roles in the pathogenesis of autoimmune disorders. As effector cells, neutrophils promote autoimmune disease by releasing cytokines and chemokines cascades that accompany inflammation, neutrophil extracellular traps (NETs) regulating immune responses through cell–cell interactions. More recent evidence has extended functions of neutrophils. Accumulating evidence implicated neutrophils contribute to tissue damage during a broad range of disorders, involving rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), primary sjögren's syndrome (pSS), multiple sclerosis (MS), crohn's disease (CD), and gout. A variety of studies have reported on the functional role of neutrophils as therapeutic targets in autoimmune diseases. However, challenges and controversies in the field remain. Enhancing our understanding of neutrophils' role in autoimmune disorders may further advance the development of new therapeutic approaches. Abstract : Various roles of neutrophils occur in autoimmune‐associated disorders, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), primary sjögren's syndrome (pSS), multiple sclerosis (MS), and crohn's disease (CD). Neutrophils play a bidirectional regulatory role in the autoimmune‐associated disorders and may serve as a predictor of disease progression. Further, increased knowledge of neutrophils' features can lead to the development of novel therapeutics.